financial marcket of central africa : structural changes and performances - (:unkn) unknown (My University, 2018)
The sub-region Central Africa, in the perspective of continuing the construction of its economic and common Monetary Area (CEMAC) strengthened has died to set up a stock exchange of Central Africa (BVMAC) for the development of its system common financial system with subregional competence.Meanwhile, one of the member countries, in this case Cameroon has a stock exchange, the Douala Stock Exchange (DSX), with the same objectives but national competence. There are therefore problems of competition, competiveness and efficiency. In short, a problem of performance of the two stock exchanges weakening the financing of its economy by the financial market to the detriment of the major potential beneficiaries that are the companies.How to structure and reorganize the financial markets of Central Africa to improve their performance in financing its economy? This question then raises the issue of the reconstruction of CEMAC’s financial markets. To answer this main question, it is necessary to take into account two constituent determinants of CEMAC:The Economic Union of Central Africa (UEAC)AndThe Central Africa Monatry Union (UMAC)In order to support four theories namely:Optimal Monetary Zone theoryCentrality theoryMutualization theoryStructural change (organization)But also empirically, to know how is organized according to the current models, that is to say the international standards of different financial markets around the world.To demonstrate the constraint of consolidating these two financial markets in the same community space on the basic of the CODERE model is strong according to Kurt Lewin (940) model and analyze their current performance. The hain borrowed from the financial integration of these financial market leads to a bipolar or multipolar specialization of this privileged development actor that is the financial market.
Keywords: African Research